Effects of STN-DBS on Depression and Cognitive Status Dementia in Patients with Parkinson’s Disease - Vahid Ghadri; Omid Rezael; Muhammad Ebrahimzadeh Mousavi; Mansour Parvaresh; Sadegh Ghadri (Budapest International Research and Critics University, 2019)
Non-motor symptoms such as depression and in later phases dementia are common features of Parkinson’s disease. For the first time in Iran, the present study aims to examine the effects of deep brain stimulation of the subthalamic nucleys (STN-DBS) on cognition and mood through neuropsychological assessment of patients with Parkinson’s disease. Stimulation of the subthalamic has no negative effect on the short-term cognitive status of patients with Parkinson’s disease, and improves depression. Precise psychological evaluation helps better recognition of the effects of this kind of surgery, which may be useful in providing quality services for those who will be candidates for this surgery in the future.